Jurnalistik Dan Minat Mahasisiwa (Studi Pengaruh Mata Kuliah Jurnalistik Terhadap Minat Mahasiswa KPI IAIDA Blokagung Banyuwangi Menjadi Jurnalis) - Abdi Fauji Hadiono (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
This research is focused to analyze the influence of journalism subjects on student interest of IAIDA KPI Blokagung Banyuwangi become Journalist. With the population as well as samples of students of IAIDA KPI Blokagung Banywangi force of 2014 which amounted to 20 students. The type of quantitative research that uses the ethical approach, in the sense that researchers collect data by first establishing the concept as the related variables derived from existing theory chosen by the researcher. Only from predetermined indicators are made questionnaires answer options and scores. In this research, the data collection by spreading the questionnaires to the IAIDA KPI IAIDA Blokagung Banyuwangi class of 2014. After analyzing the data collected, the researcher found that there is influence between journalistic subjects (X) on the interest of IAIDA KPI student BLokagung Banyuwangi become a journalist by using correlation test Pearson Product Moment is quite strong. The conclusion is: "There is a significant influence between Journalism Subjects to Student Interest KPI IAIDA Blokagung Banyuwangi become Journalist